Odpowiedź :
a)
[tex]3 = 2x + 7[/tex]
L = 3
P = 2x + 7 = 2 × (-2) + 7 = -4 + 7 = 3
L = P
Tak
b)
[tex]6 - 4x = 2[/tex]
L = 6 - 4x = 6 - 4 × (-1) = 6 + 4 = 10
P = 2
L ≠ P
Nie
c)
[tex]7 = - 5x - 8[/tex]
L = 7
P = -5x - 8 = -5 × (-3) - 8 = 15 - 8 = 7
L = P
Tak
d)
[tex]9x + 6 = - 28[/tex]
L = 9x + 6 = 9 × (-4) + 6 = -36 + 6 = - 30
P = -28
L ≠ P
Nie
Odpowiedź:
[tex]a)\ \ 3=2x+7\ \ \ \ \ \ x=-2\\\\L=3\\\\P=2x+7=2\cdot(-2)+7=-4+7=3\\\\L=P\\\\Odp.\ \ x=-2\ \ jest\ \ rozwiazaniem\ \ danego\ \ r\'ownania\\\\\\b)\\\\6-4x=2\ \ \ \ \ \ x=-1\\\\L=6-4x=6-4\cdot(-1)=6+4=10\\\\P=2\\\\L\neq P\\\\Odp.\ \ x=-1\ \ nie\ \ jest\ \ rozwiazaniem\ \ danego\ \ r\'ownania[/tex]
[tex]c)\ \ 7=-5x-8\ \ \ \ \ \ x=-3\\\\L=7\\\\P=-5x-8=-5\cdot(-3)-8=15-8=7\\\\L=P\\\\Odp.\ \ x=-3\ \ jest\ \ rozwiazaniem\ \ danego\ \ r\'ownania\\\\\\d)\ \ 9x+6=-28\ \ \ \ \ \ x=-4\\\\L=9x+6=9\cdot(-4)+6=-36+6=-30\\\\P=-28\\\\L\neq P\\\\Odp.\ \ x=-4\ \ nie\ \ jest\ \ rozwiazaniem\ \ danego\ \ r\'ownania[/tex]